Emerging Spectrum of Perforation Peritonitis in Developing World - Hameed, Tariq; Kumar, Awadh; Sahni, Shivanand; Bhatia, Rahul; Vidhyarthy, Ajit Kumar (Frontiers in Surgery, 2020)
Background Gastrointestinal perforations constitute major cause of acute abdomen coming to surgery emergency room. Incidence, site of perforation and age is different in developing world and is showing new trends. Etiological spectrum in developing world is different from western world. This study was conducted to find out the latest trends in perforation peritonitis in India. Methods This study was conducted in a single surgical unit of Darbhanga Medical College and Hospital, India. A total of 350 consecutive patients of perforation peritonitis were studied in terms of age, sex, seasonal variation, biochemical parameters, clinical presentation, radiological and intraoperative findings, surgical intervention done and post operative outcome. Results Most common cause of perforation peritonitis in our study was duodenal ulcer(~50%) followed by typhoid(20%), traumatic(14.5%), appendicular(7.4%) and tubercular(3.1%). Males were three times more commonly affected than females. Peak incidence was noted in 2nd and 3rd decade of life. Peptic ulcer perforations were common in autumn and winters and typhoid perforations were common during summer and rainy seasons. Conclusion Spectrum of perforation peritonitis cases in this part of world is different from developed western countries. It is different in respect of younger age at presentation, site of perforation and etiological factors. Infective pathology makes up to a quarter of total cases in developing world. Developing world has more perforation peritonitis cases involving upper gastrointestinal tract, while western world has dominance of lower gastrointestinal tract perforations.